(untitled) (American Journal of Research in Humanities and Social Sciences, 2022)
The article expresses the importance of the “Mahalla” and the family institutions in ensuring information security, especially in the years of independence, discusses the laws developed to improve the efficiency of these institutions and the wide opportunities that open up. And also, recommendations are given for solving problems associated with these cases.